UMPSA forges sustainability cooperation with Tanah Makmur Berhad - Naqiah, Puaad (UMPSA, 2024)
PEKAN, 26 June 2024 – The Memorandum of Understanding (MoU) Exchange Ceremony between Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) and Tanah Makmur Berhad (TMB), along with a Sharing Session by the Chief Executive Officer of TMB, Dato' Shahrul Nizam Abdul Aziz, took place at the UMPSA Banquet Hall recently